Demonstration of variation in chondrocyte activity in different zones of articular cartilage: an assessment of the value of in-situ hybridization. - Marles, P. J. (1991)
Several methods have been described for investigating chondrocyte metabolism in vitro. In this study, in-situ hybridization (ISH) using an oligonucleotide probe (i.e. a poly-d(T) probe) to detect total messenger RNA (mRNA) in cartilage explants has been compared with radiosulphate and radioleucine uptake studies in an attempt to assess the value of ISH in investigating chondrocyte metabolism. The relative results of the three parameters indicate qualitative similarities in cells in the intermediate, deep and calcified zones but differences in the superficial zone. The relative levels of mRNA and leucine and sulphate uptake in the midzone areas could be construed as indicating that the bulk of cellular activity was directed towards the synthesis of proteoglycans. A similar relation between the three parameters, but at a lower level, was seen in chondrocytes in the calcified zone demonstrating that these cells are viable and biosynthetic. Both quantitative and qualitative differences between the three methods were observed in the superficial chondrocytes regarding the amount of mRNA compared to sulphate and leucine uptake. The results suggest that ISH can detect differences in the amount of mRNA present in chondrocytes in differing zones of cartilage and, like the radioleucine and radiosulphate studies, particularly emphasizes their functional heterogeneity.